Sosok Guru Idola Siswa Jaman Now - Patricia Menge (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
This study discusses the figure of today's student idol teachers and how students perceive, assess, and describe the figure of their idol teachers. This research was conducted using a qualitative method of case study approach with the aim of getting a more detailed and in-depth picture of the characteristics of the figure of the idol teacher that is considered important by students, as well as their contribution in motivating students to learn and develop. Behavioristic theory is used to understand the importance of input that stimulates or stimulates a person to behave by diagnosing positive things in the individual. This research is expected to provide input for the development of education in today's digital era.